Analisis Harga Pokok Produksi Berdasarkan Pesanan Untuk Menentukan Harga Jual Produk Pakaian Di Ampera Manna Bengkulu Selatan - Helmarini Helmarini; Nike Ardila (Universitas Dehasen Bengkulu, 2022)
The purposes of this study are: 1) to determine the calculation of the cost of production based on orders for clothing production at Raffi's shop (2) to determine the selling price of clothing production at the Ampera Manna Market, South Bengkul. Data collection techniques used in this study were observation, interviews and documentation. In this study, quantitative descriptive data analysis techniques are analytical techniques whose measurements use numerical calculations to see the cost of production produced using the full costing formula or method. Based on the results of this study, it can be said that: The production of making clothes at Raffi's shop uses the stages in setting the selling price by adding up the production costs or dividing by the number of products. In this study, the authors set the selling price by calculating the entire cost of production using the full costing and variable costing methods which the authors hope can help the production of clothing at Raffi's shop get a good profit, from the results of the pricing, the price setting for clothes with semi-wool raw materials is obtained. amounting to RP 2,431,000 while according to the variable costing method of Rp 2,403,000. This difference is caused because the variable costing method does not calculate in detail the fixed factory overhead costs. While the method of calculating the overall cost of the price as an input in setting the selling price wants to get a good profit and can cover all production costs to be able to maintain its business continuity. The price setter using full costing can determine the desired selling price for the suit product. the shop Raffi took the expected profit of 20%.